Ground‐Based GNSS and C/NOFS Observations of Ionospheric Irregularities Over Africa: A Case Study of the 2013 St. Patrick’s Day Geomagnetic Storm - P. O. Amaechi; E. O. Oyeyemi; A. O. Akala; H. E. Messanga; S. K. Panda; Gopi K. Seemala; J. O. Oyedokun; R. Fleury; C. Amory‐Mazaudier (Space Weather)
Abstract In this paper, the variations of ionospheric irregularities have been studied using C/NOFS, ground‐based GNSS and magnetometer measurements in Africa during the St. Patrick geomagnetic storm of March 17, 2013. The latitudinal distribution of irregularities was examined using GNSS‐ROTI maps covering longitude 25°–45°E. Longitudinal characteristics were also investigated along with equatorial plasma bubbles (EPBs) and vertical drift velocity (Vz) from 12 to 21 March 2013. The results show postsunset irregularities from 12°S–27°N with the stronger ones confined within 1°S–7°S and 12°N–22°N in the prestorm period. The observed pre‐reversal enhancement (PRE) with Vz varying from 22.51–59.47 m/s between 20.26 and 20.86 LT corresponded with the occurrence of EPBs. PRE greater than 40 m/s nevertheless, supported long lasting depletions. During the main phase, prompt penetration electric field enhanced the PRE thus, extended the latitudinal range of irregularities to 31°N. It also induced a long duration EPB along 15°E and several depletions over the Eastern sector. During the recovery phase, stormtime wind drove a conspicuous asymmetry in the morphology of the postsunset anomaly. This corresponded with the reduction in the latitudinal extent and strength of irregularities. Westward/eastward disturbance dynamo electric field inhibited/triggered irregularities in the postsunset/postmidnight period on 18 March over the Eastern sector. The difference in the drift accounted for the longitudinal variations of irregularities before the storm. During the main phase however, irregularities were present (reduced) over the Eastern (Atlantic/Western) sectors. This difference might have been related to the changes in the wind inferred from the anomaly shape.